Social Theory, Photography and the Visual Aesthetic of Cultural Modernity. (June 2020) - Ray, Larry
Social theory and photographic aesthetics both engage with issues of representation, realism and validity, having crossed paths in theoretical and methodological controversies. This discussion begins with reflections on the realism debate in photography, arguing that beyond the polar positions of realism and constructivism the photographic image is essentially ambivalent, reflecting the ways in which it is situated within cultural modernity. The discussion draws critically on Simmel's sociology of the visual to elucidate these issues and compares his concept of social forms and their development with the emergence of the photograph. Several dimensions of ambivalence are elaborated with reference to the politics and aesthetics socially engaged photography in the first half of the 20th century. It presents a case for the autonomy of the photographic as a social form that nonetheless has the potential to point beyond reality to immanent possibilities. The discussion exemplifies the processes of aesthetic formation with reference to the 'New Vision' artwork of László Moholy-Nagy and the social realism of Edith Tudor Hart.